Russia Economic Report, No. 42, December 2019 : Weaker Global Outlook Sharpens Focus on Domestic Reforms - World Bank Group (World Bank, Moscow, 2020)
After a weak performance in the first half of 2019, helped by monetary easing, faster public spending and some one-off effects, economic growth in Russia picked up in the third quarter at 1.7 percent, y/y. Consequently, our 2019 forecast has been revised upwards to 1.2 percent (from its previous reading of 1 percent). Globally, growth has weakened substantially in 2019, reflecting a broad-based slowdown in industrial activity and global trade. Slowing external demand and the OPEC agreement weighed on Russia's exports performance. Crude oil prices fell 14 percent in January-September 2019, y/y, reflecting a downturn in the world economy.